Polynomic Behavior of Nitrous Oxide Emission in Coffee Plantations in Costa Rica - Montenegro-Ballestero, Johnny (2019)
Nitrous oxide is a powerful greenhouse gas that is generated both by natural processes and by agricultural practices such as nitrogen fertilization. For this reason, the emission of N2O was quantified by the application of urea nitrogen (0, 100, 225 and 350 kg ha-1 a-1) to coffee plantations in two coffee producing regions of Costa Rica (Valle Occidental and Los Santos). The emission was quantified during an agricultural year. Results showed the effect of rainfall on N2O emission; regardless of the dose, the highest emission occurred during the first days after fertilizer application. In Valle Occidental, the highest emission of N2O was detected with 350 kg of N ha-1 a-1, and intermediate levels with 100 and 225 kg of N ha-1 a-1. The lowest emission was found without fertilization. These results were used to derive a polynomial model (Y=8E-08x3-4E-05x2+0.0064x+0.6266, r2=0.87). In Los Santos, emission was lower without fertilizer; the highest levels were found with 350 kg of N ha-1 a-1. Emissions with 100 and 225 kg of N ha-1 a-1 were similar, although different from the other treatments. A polynomial model was derived using this data (Y=-3E-06x2+0.0023x+0.6347, r2=0.87). With the data of both localities a polynomial model was derived (Y=6E-08x3–3E-05x2+0.0052x+0.6247, r2=0.83). Use of this information is recommended to estimate the N2O generated by urea application to coffee plantations.